Teaching Mathematics in traditional indigenous villages do Alto Xingu, in Mato Grosso State, Brazil (Research, Society and Development, 2020)
The Master's research in development belongs to the Graduate Program of the University of Cuiabá. With the conquest of the right to a differentiated educational institution, guaranteed by the Federal Constitution of 1988, attention has been focused on the Mathematics model that is taught in indigenous schools, as well as the search for content and materials for the formulation of curricula of indigenous school institutions. . In view of this statement, the purpose of this article is to reflect on the teaching of mathematics in indigenous villages and how students learn the basic mathematical concepts to apply in everyday situations. The method is anchored in ethnographic study and field research as an epistemological contribution and mediator of activities inside and outside the classroom. The previously analyzed data reveal that mathematics is present in the most common everyday actions of indigenous villages, with emphasis on the measurement system for the construction of Oca. The fathom is used as a unit of measurement of length that is equivalent to the linear meter, an ancient practice widely used with property in today's indigenous communities. Another highlight is the daily actions that involve various mathematical concepts where collective coexistence and cultural habits require daily.